Social Status Reflected in Jane Austen's Emma - Mela Krismawati; Emil Eka Putra (Humanitatis : Journal of Language and Literature, 2021)
Abstract This research discusses the social status of society at Highbury in the era of the 19th century. In this research the writer using the qualitative method to analyze social status that reflected in Jane Austen’s Emma and apply the theory of Swingewood (1972), that is the sociology of literature or the sociological approach. The result of this research that obtained the social status is still upheld by the community as a culture that they must preserve. When choosing a life partner, it is often determined by the background of both parties. If both parties do not have a match in their background then their wedding will not be permanent and happy. Because a person's social status is made the key as a part of a relationship, both in love and marriage. Marriage and love relationships are motivated by social class and work. Meanwhile, based on this culture it leads to the opinion that the upper class is not worthy of having a love relationship with the lower class. Keywords: social status, happy, marriage, and love